Hubungan Pola Asuh Orang Tua dengan Disiplin Siswa ditinjau dari Jenis Kelamin Anak - Rachmaniar, Ananda; Albari, Muhammad Ridho; Alfirazi, Diova Laviria; Thahir, Muthahharah; Salis, Asyifa Ismi; Putri, Arini Berliana (Universitas Muhammadiyah Metro, 2026)
Despite extensive research on parenting styles and student discipline, empirical studies that explicitly examine gender-based differences in this relationship remain limited, particularly at the junior secondary school level in Indonesia. This study aims to address this gap by investigating the relationship between parenting styles and student discipline when viewed from the child’s gender, thereby offering a more nuanced understanding of parental influence in character development. A quantitative correlational design was employed involving 212 ninth-grade students of SMP Al-Ma’soem in the 2025–2026 academic year, consisting of 124 male students and 88 female students. Data were collected using validated and reliable Likert-scale questionnaires measuring parenting styles and student discipline. Spearman rank correlation analysis revealed a positive and statistically significant relationship between parenting styles and discipline among male students (ρ = 0.177; p = 0.049), although the strength of the relationship was very low. In contrast, no significant relationship was found among female students (ρ = 0.024; p = 0.826). These findings highlight gender-specific patterns in the association between parenting styles and student discipline, suggesting that parental influence tends to be more salient for male students, while female students’ discipline may be shaped more strongly by internal regulation and broader environmental factors. The study contributes theoretically to guidance and counseling literature by emphasizing the importance of incorporating gender perspectives in parental involvement strategies aimed at fostering student discipline.